Pemanfaatan Photo Editing App: Media Belajar Menyusun Teks Iklan Berbasis Gawai Kelas VIII MTsN 5 Magelang - Arika Rini (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2023)
This research aims to determine the use of the Photo Editing App as a learning medium for compiling device-based advertising text and determine the results of class VIII students at MTs Negeri 5 Magelang in compiling advertising text using the Photo Editing App. This research uses a quantitative descriptive method, namely testing hypotheses by describing certain variables in the form of numbers as a result of data collection. The data population is students at MTs Negeri 5 Magelang with a sample of 58 students in class VIIIC and VIIID at MTs Negeri 5 Magelang. Data collection was carried out using observation techniques and product tests. Observations were carried out to determine students' activities when working on assignments from the download stage to the stage of sending assignments to the Google Drive link. Product tests were carried out to obtain value data obtained by students in the task of compiling advertising texts using descriptive statistical data analysis techniques, namely by describing data from tables. The research results prove that students can use the Photo Editing App, it is proven that students can go through the stages of the application. All students get scores above the KKM. The average achievement score for each class has exceeded the KKM, class VIIIC has an average of 85 and VIIID has an average of 86.